INVESTIGATION OF THE MINERAL CONTENTS OF SOME VARIETIES OF POWDER MILK BY PIXE - Ahmad, N.; H. Aejaz, S. M.; Naeem, A.; Shahnawaz, M.; Saadat, S. (The Nucleus, 2010)
Milk and milk products constitute an important ingredient of human nutrition all over the world. Macro mineral contents like sodium, potassium, calcium, phosphorus and micro mineral contents like iron, copper, zinc, manganese of some varieties of powder milk available in the local market have been investigated by Proton Induced X-Ray Emission (PIXE). These elements are essential for the optimal functioning of various chemical processes taking place in the human body. Any toxic element present in milk can also be detected simultaneously. PIXE is a powerful and universal elemental analysis technique with high detection sensitivity for elements with Z> 11 in the periodic table. The technique is non-destructive and may be applied to samples as small as a cell to a large painting.